TINGKAT HUBUNGAN ANTARA VARIABEL PENDUGA BOBOT DAGING (CARCASS CUTABILITY) KARKAS SEGAR SAPI SIMPO DAN LIMPO JANTAN - Awistaros Angger Sakti; Panjono Panjono; Rusman Rusman (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Estimation of carcass cutability is an important factor in beef marketing. This research was conducted to observe the relationship among variables of carcass cutability estimation in hot carcass of SimPO (Simmental-Peranakan Ongole) and LimPO (Limousin-Peranakan Ongole) cattle. Eighty three bulls were used, consisted of 51 SimPO and 32 LimPO cattle. The data collected were age, body weight, carcass weight (X1), fat thickness (X2), ribeye area (X3), percentage of visera fat (X4), and carcass cutability. The data were analyzed using Independent Sample T-test, correlation 2-tailed, enter and stepwise regression analysis, and estimation curve. There were no different of age, body weight, X1, X2, X3, X4, and carcass cutability among SimPO and LimPO. There was a positive correlation between X1, X2, X3, X4 and carcass cutability (P<0,05), except to LimPO which had negative correlation for X4. The regression equation and determination coefficient of SimPO and LimPO were Y=-24,726+0,916X1; R2=0,948 and Y=-28,461+0,929X1; R2=0,996, respectively. The result indicated that the best equation for SimPO was a linear equation (R2=0,948), and a quadratik equation (R2=0,996) for LimPO.